2021
DOI: 10.1080/1331677x.2021.1941181
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and stock market nexus: evidence from Shanghai Stock Exchange

Abstract: The outbreak of the contagious pandemic Covid-19 has disturbed various economic and business activities across the globe. This has resulted in the declination of cash flows and revenues, which significantly increases the probability of corporate bankruptcies and adversely affects the stock market performance. The current study investigated the Covid-19 and stock market nexus whilst considering the Shanghai Stock Exchange (SSX). Covid-19 active cases and deaths have been considered proxies for the Covid-19 from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…(Khan et al, 2020). Several previous studies identified the impact of rising Covid-19 cases on the stock market in several countries when the Covid-19 pandemic was taking place, such as the results of research by Priyono (2022), Kamaludin et al (2021), Li et al (2021), and Udeaja and Isah (2021). These studies found a negative effect on the increase in Covid-19 cases on stock indices because it impacted the performance of the companies being invested.…”
Section: Effect Of the Covid-19 Pandemic On Stock Indicesmentioning
confidence: 96%
“…(Khan et al, 2020). Several previous studies identified the impact of rising Covid-19 cases on the stock market in several countries when the Covid-19 pandemic was taking place, such as the results of research by Priyono (2022), Kamaludin et al (2021), Li et al (2021), and Udeaja and Isah (2021). These studies found a negative effect on the increase in Covid-19 cases on stock indices because it impacted the performance of the companies being invested.…”
Section: Effect Of the Covid-19 Pandemic On Stock Indicesmentioning
confidence: 96%
“…To fill this lacuna, we explore the nexus between financial structure and health outcomes in China (31). In this study, financial structure is measured by two proxy measures: stock market capitalization and stock market turnover (32). Health outcome is measured by infant mortality rate and life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…The great depression was endogenous in nature due to the bad decisions of stakeholders. Whereas, COVID-19 is exogenous in nature as it has affected the real economies and stock indexes (Li, Su, Altuntaş, & Li, 2021).…”
Section: Introductionmentioning
confidence: 99%